A novel approach for the determination of exchangeable copper in serum using protein precipitation. Issue 3 (19th January 2023) - Tuchtenhagen, Max; Stiboller, Michael; Witt, Barbara; Schwerdtle, Tanja
Abstract : A novel method for the determination of exchangeable copper has been developed based on protein precipitation. This method serves as an alternative to common ultrafitration based methods. Abstract : Copper (Cu) is an essential trace element with tightly regulated homeostasis in the body. Alterations in homeostasis may have severe consequences for human health. Diagnosis of Cu dyshomeostasis by assessment of a reliable biomarker at an early stage is crucial to prevent the onset or to monitor the progression of Cu-related diseases. A novel promising diagnostic biomarker for the individual Cu-status is the exchangeable copper (CuEXC) in serum, representing the labile Cu fraction not tightly bound to ceruloplasmin and the relative exchangeable copper, derived from CuEXC and total serum Cu. CuEXC in serum is easily extracted with chelators like ethylenediaminetetraacetic acid (EDTA) but separation from serum proteins by commonly used ultrafiltration is problematic. We present the development and validation of a novel approach for the determination of CuEXC in human serum combining EDTA-complexation with separation by protein precipitation followed by a flow-injection analysis with detection by inductively coupled plasma tandem mass spectrometry.